Teleodontologia para o rastreio do câncer de boca em idosos - Gondim, Flávio Murilo Lemos (2023)
Introduction: Cancer is a major public health problem and one of the four leading causes of death before the age of 70. Currently, cancer incidence and mortality are on the rise, both due to ageing and population growth, and due to changes in the population's habits, especially those related to socioeconomic development. Among the various types of cancer, oral cancer accounts for 3% of all cases worldwide, with Brazil being one of the countries with the highest prevalence. Although the initial lesions of oral cancer are easily detectable, they are still diagnosed late. This highlights the need to adopt screening measures so that the pathology can be diagnosed early. Objective: to apply Teleodontology in the screening of oral cancer in the elderly, carrying out a systematic review for theoretical basis, developing an Action Plan to implement a mobile application for screening oral cancer in the elderly and using Teleodontology in this process. Method: The study consisted of three stages. In the first stage, a systematic review on Teleodontology in the screening of oral cancer in the elderly, was carried out following the recommendations of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). In the second stage, an Action Plan was drawn up for the implementation of a mobile application for screening mouth cancer in the elderly. The third stage involved training community health workers to use teleodontology. Results and Discussion: The following were produced: 1) Systematic review article entitled “Teleodontology in oral cancer screening: a systematic review”. 2) Action Plan for implementing teleodontology in oral cancer screening in the municipality of Pedras de Fogo-PB. 3) Training for the health team that will operate the screening tool. 4) Instructional video presenting the application's interfaces, as well as how to use it in the community. 5) Data processing policy. 6) Questionnaire administered to 71 community health agents. Final considerations: The systematic review showed that Teleodontology contributes to oral cancer screening, since by overcoming physical distance and the unequal distribution of dental surgeons, it makes it possible for users to have greater access to the health system in a shorter space of time, making it a viable tool from an economic and ethical point of view for achieving early diagnosis. In turn, the Action Plan made it possible to materialize the knowledge previously acquired, using the screening tool and relying on the integration of other professionals in order to change the local reality with regard to mouth cancer.